Metal oxide modified limestone catalysts for gasification of rice straw in hydrogen production - Mohamad @ Mahmud, Surahim (2016)
Hydrogen has great potential for energy and environmental sustainability. Hydrogen is considered as a secondary source of energy, commonly referred to as an energy carrier which is used to store and transport energy in a form that can be easily used. Hydrogen does not exist freely in nature, it only produced from other sources. The potential of utilization of biomass as renewable and sustainable energy resources have attracted researchers to produce hydrogen from cheap and highly available resources such as lignocellulosic biomass waste. Biomass gasification of rice straw using modified natural limestone based catalysts has been studied to promote the production of hydrogen. This study is aimed to develop natural calcined limestone (CL) based catalysts with high activity and selectivity. Modification with addition of mono and bimetallic metal dopants (Ni, Fe, Co, NiCo, NiFe and CoFe) on CL were performed for gasification of rice straw biomass for hydrogen conversion. The catalysts were synthesized through wet impregnation method and characterized by using X-ray diffraction (XRD), Brunauer-Emmett-Teller (BET) surface area, Thermogravimetry analysis (TGA), Field emission scanning electron microscopy - Energy dispersive Xray (FESEM-EDX) and Temperature programmed desorption of carbon dioxide (TPDCO2) to determine the structure, physical and chemical properties of the catalysts. Temperature programmed gasification (TPG) was conducted to investigate the gasification reaction of rice straw and the product gases were analysed using online mass spectrometer. The gasification process was carried out in partial oxygen (5% O2/Helium) environment heating from 50 to 900 °C with mass ratio of biomass to catalyst of 2:1. The results revealed that the addition of metal dopants on CL significantly improves the activity and selectivity towards hydrogen production. For monometallic doped catalysts, Ni-CL was found to give the highest H2 conversion followed by Co-CL and Fe-CL. Moreover, The CL had shown to act both as catalyst and CO2 sorbent thus enhanced the production of hydrogen. The additions of bimetallic dopant have shown a further increment of hydrogen yield. The NiCo-CL catalyst exhibit highest hydrogen selectivity compared to other catalysts due to improvement in catalytic activity that enhanced gasification of rice straw and promoted hydrogen favoured reactions.